Perspektif Kitab Undang – undang Hukum Perdata Terhadap Kontrak Antara Yayasan Sahabat Keluarga Daycare Bintang Al-Qur’an Dengan User Tentang Penitipan Anak - Djawas, Nur Nakiyah Fatliyah; Mauritsius, Darius; Damat, Petornius (Law Faculty, Nusa Cendana University, 2024)
This study aims to analyze the perspective of the Indonesian Civil Code (KUHPerdata) on binding contracts between the Sahabat Keluarga Daycare Bintang Al-Qur’an Foundation and service users (parents) in childcare. This research employs a normative empirical legal approach, combining theoretical studies with field data collected through interviews and observations at the daycare. The findings indicate that the contract plays a crucial role in defining the rights and obligations between both parties, while providing legal protection for those involved. In practice, the contract at Bintang Al-Qur’an daycare has not fully complied with the formal and substantive requirements stipulated in KUHPerdata, which poses potential legal risks, especially if there is any violation of children's rights or unlawful acts. This research is expected to serve as a guide for daycare management to formulate more comprehensive contracts in accordance with civil law principles.